INFLUENCE OF SOIL COVER ON ORGANIC MATTER AND EDAPHIC VARIABLES IN ITATIAIA-RJ NATIONAL PARK - Medeiros, Alexandre dos Santos; Pereira, Marcos Gervasio Gervasio; Anjos, Lúcia Helena Cunha dos; Fréo, Vanessa Aparecida (Floresta, 2020)
Forest ecosystems in the Middle Valley region of Paraíba do Sul have undergone profound changes throughout history. Currently, degraded pastures and secondary forest fragments predominate in different successional stages, responsible for numerous environmental services, among them the sequestration and stabilization of CO2. In order to understand successional processes, their influence on soil variables and soil organic matter (SOM), different land uses and geomorphological diversity must be considered, since environmental variability can influence this dynamic. The objectives of the study were to evaluate physical and chemical variables and the organic matter of soils located in the southern slope of the Itatiaia National Park (RJ); as well as to characterize possible patterns under coverings of Dense Ombrophilous Forest and pastures and indicate which cover would accumulate the highest levels of carbon (C) and in its most stable forms. The pasture areas had the highest C averages, but more stable fractions of SOM were found in the different stages of forest succession. An increase in SOM stability was also observed due to the progression of successional stages.